THE ROLE OF ENTREPRENEURSHIP IN POVERTY ALLEVIATION: AN EVALUATION OF COMMUNITY ECONOMIC EMPOWERMENT PROGRAMS AND POLICIES - Setiawan, Bambang (Journal of Islamic Economic Development, 2024)
This study aims to evaluate the role of entrepreneurship in poverty alleviation through an analysis of community economic empowerment programs and policies. The research method used involves a literature study as well as an empirical data search related to the implementation of economic empowerment programs in various regions. The results show that entrepreneurship plays an important role in improving people's economic welfare by creating jobs, increasing access to capital, and encouraging innovation. However, the evaluation also revealed several challenges, such as lack of government support, limited technological infrastructure, capital constraints, and lack of social marketing strategies in rural areas. Therefore, this study suggests the need for collaboration between the government, private sector, and communities in implementing effective economic empowerment policies to address poverty in a sustainable manner.